Application of toluidine blue stain and neuron specific enolase immunohistochemical stain in the diagnosis of hirschsprung disease - Tasmia Islam; Sultana Gulshana Banu; Bishnu Pada Dey; Mohammad Mosiur Rahman; Papiya Rahman; Ummey Salma Shabnam; Syeeda Shiraj Um Mahmuda (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Hirschsprung disease is one of the most common and problematic infancy and childhood maladies. Early and accurate diagnosis is a fundamental step in proper management and prevention of complications. The most reliable method for diagnosis is the histopathological analysis of colorectal biopsies and the typical finding of Hirschsprung disease is the absence of ganglion cells. Toluidine blue stain can act as a double check along with conventional H&E stain for ganglion cell detection. Neuron-specific enolase is an immune-histochemical marker that can also aid in better identifying ganglion cells, especially for small and immature ones. This study aimed to evaluate Toluidine blue stain and Neuron specific enolase immunostain along with conventional H&E stain as a panel for the diagnosis of Hirschsprung disease. This cross-sectional study was conducted from September 2019 to August 2021, involving 55 clinically suspected Hirschsprung disease cases. Paraffin blocks of colorectal biopsy samples were collected from the Department of Pathology, BSMMU. Hematoxylin & Eosin, Toluidine blue stain, and Neuron specific enolase immunohistochemical stain for Hirschsprung disease detection were performed on the sections from the paraffin blocks. Then the sections were examined and an evaluation of the stains was done. Statistical analysis was performed on the tabulated data by chi-square test. Among 55 cases, conventional H&E stain detected ganglion cells in 31 cases, that is 56.4%. Later, Toluidine blue stain and Neuron specific enolase immu- nohistochemical stain detected ganglion cells in 35 cases, that is 63.6%. So, these two addition- al stains were able to detect ganglion cells in four more cases compared to conventional H&E stain. In conclusion, conventional H&E stain, Toluidine blue stain, and NSE immunohisto- chemical stain can improve the diagnostic accuracy of Hirschsprung disease.